BENTUK PENYAJIAN TALEMPONG PACIK DALAM ACARA BABAKO DI KOTA PAINAN KABUPATEN PESISIR SELATAN - Gema Umanda; Jagar Lumbantoruan; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2018)
AbstractThis article aimed to describe the presentation of talempong pacik in Painan, Pesisir Selatan district seen at the babako event. The approach of this research used descriptive analysis method. The results of the study found that there were 3 procession stages at the Babako event: a) Balimau, b) Maasok Kumayan and c) having meal together. The presentation of talempong pacik at babako event is performed as a form of procession. It is as an accompaniment of bako picking up the bride (anak daro) and the groom (marapulai). Talempong pacik is begun with the bride-groom parade to the bride's house. Next, it is continued by the babako procession and then the parade goes back to the bride’s house. Talempong pacik is showed to the public as a performance. The meaning of the talempong pacik is a symbol of happiness for the bride and groom's family and it is a manifestation of Painan people’s love for traditional arts, especially talempong pacik.Keywords: The Form, Talempong Pacik, Babako Event.